The status of the programs of preparing English language teachers in the light of NCATE Standards at Palestinian universities, Ghaza - Fayiz Kamal Shaladan; bed Elkareem Abulila (University of Science and Technology, Yemen, 2017)
The study aimed to identify the status of the programs of preparing English teachers at the Palestinian Universities in the light of NCATE standards and the ways to improve them.  In order to achieve the objectives of the study the researchers used  the descriptive analytical approach. The study sample consisted of (46) English teachers from Palestinian Universities. The researchers used the questionnaire as a main tool for collecting data. They also used the interview as a secondary tool, in order to know how  to improve the status of the programs of preparing English teachers in Gaza Governorates. The study revealed a number results, including the following: The total score of the current status of the programs of preparing English language teachers in the light of NCATE standards was 68.42%, which could be considered high. ·        There are statistically significant differences  due to the university in all areas in favor of Al-Quds Open University, except the fifth area (the staff) which came in favor  of Al-Azhar University. There are no significant differences due to the years of service. Submitting proposals to improve teachers of English preparation programs. The study recommended Palestinian universities to make the best use of modern experiences to improve such programs, and to have professional development programs for the members of English teaching staff through training workshops. Keywords: Programs of preparing English teachers, English language teachers, Palestinian universities, NCATE standards.